Efectos peligrosos en presencia de arcos eléctricos en tableros de distribución - Gallo, Juan (2010)
This project consists fundamentally on the quantitative analysis of the risk of burns by an Arc Flash in a distribution board like implementation of Electric Security in the industry IPAC S.A. The technical data were obtained of the main board distribution of Plant 2 and to their development we have based on norms and codes like NFPA and IEEE where their takes in consideration the worker's obligations and the employer. At the end of this analysis the levels of incident energy (burns) will be measured in a person could be subjected if doesn't have the due preparation or use of appropriate EPP.